Efektivitas Legal Awareness Legal Obedience Masyarakat dan Pemerintah Sebagai Faktor Tegaknya Negara Hukum di Indonesia - Ahmad Nurun (Jurnal Sociohumaniora Kodepena (JSK), 2025)
The progress of a nation can be seen from the level of legal awareness and legal obedience of its citizens. The higher the legal awareness and legal obedience of a country's population, the more orderly the life of society and the state will be. The factor of legal awareness and legal obedience plays an important role in the development of law, meaning that the weaker the level of legal awareness of society, the weaker the legal strictness, conversely the stronger the legal awareness, the stronger the legal obedience factor. Indonesia as a country of law. This statement indicates that all actions must be based on the legal principles of the rule of law as stated in Article 1 paragraph (3) of the 1945 Constitution. However, in Indonesia there are still many cases of legal violations committed by state officials such as the Ferdi Sambo case, as well as the case of the mutilation of a wife by her husband TBD in Ciamis, etc. Therefore, it is necessary for the author to conduct further research using empirical legal research methods using a juridical and sociological approach to measure the impact and effectiveness of Legal Awareness Legal Obedience of Society and Government as a Factor in Upholding the Rule of Law in Indonesia. Legal awareness from the community and government requires several efforts hard work and strategy in enforcing the law in Indonesia and cannot be separated from the ability and strong will of various elements both from the community and the government because it is the key to upholding the law in Indonesia so that it will lead to order and progress.